Disease-mediated inbreeding depression in a large, open population of cooperative crows - Townsend, Andrea K. (The Royal Society, 2009)
Disease-mediated inbreeding depression is a potential cost of living in groups with kin, but its general magnitude in wild populations is unclear. We examined the relationships between inbreeding, survival and disease for 312 offspring, produced by 35 parental pairs, in a large, open population of cooperatively breeding American crows (Corvus brachyrhynchos). Genetic analyses of parentage, parental relatedness coefficients and pedigree information suggested that 23 per cent of parental dyads were first- or second-order kin. Heterozygosity–heterozygosity correlations suggested that a microsatellite-based index of individual heterozygosity predicted individual genome-wide heterozygosity in this population. After excluding birds that died traumatically, survival probability was lower for relatively inbred birds during the 2–50 months after banding: the hazard rate for the most inbred birds was 170 per cent higher than that for the least inbred birds across the range of inbreeding index values. Birds that died with disease symptoms had higher inbreeding indices than birds with other fates. Our results suggest that avoidance of close inbreeding and the absence of inbreeding depression in large, open populations should not be assumed in taxa with kin-based social systems, and that microsatellite-based indices of individual heterozygosity can be an appropriate tool for examining the inbreeding depression in populations where incest and close inbreeding occur.